Critical decision of operability in congenital heart disease patient with severe pulmonary hypertension - Joshi, Raja (Ann Card Anaesth, 2016)
Repair of congenital heart disease in the presence of high pulmonary pressure has always been a contentious issue. Pulmonary vascular resistance (PVR) is considered important for establishing operability in these patients. However, PVR estimation is not always accurate and cannot solely be relied upon to make critical decision of operability. Clinical examination, chest X-ray, and echocardiography are also important indicators of pulmonary vascular disease. Knowledge of pits and falls of each investigation is important for appropriate management in these patients. We present a case report of successfully operated, 6-year-old child with anomalous origin of the right pulmonary artery from aorta, deemed inoperable on the basis of PVR estimation.